Comparison of the distances of the three jumps of the Iraqi champions in the effectiveness of the triple jump with the distances of the international ratios (horizontal – vertical( - Fereydoun Hassan Othman; Sirwan Karim Abdullah (Zanco Journal of Humanity Sciences)
The research aims to: